Analisis Faktor Yang Mempengaruhi Integritas Laporan Keuangan Perusahaan Manufaktur di Indonesia - Lilis Setyowati; Nurmansyah Perkasa Ricky Setiawan (BADAN PENERBIT STIEPARI PRESS, 2022)
Financial reports have a very important role for users of financial reports to obtain information that will be used as material for consideration in decision making. This study aims to determine the effect of the level of institutional ownership, managerial ownership, independent commissioners, and audit committees on the integrity of financial reports in manufacturing companies listed on the IDX in 2015-2019. The data was taken through purposive sampling technique and obtained as many as 44 company samples. The collected data were analyzed using multiple linear regression analysis which was processed using SPSS. The results of the analysis show that managerial ownership and independent commissioners have an effect on the integrity of financial reports, while institutional ownership and audit committees have no effect on the integrity of financial reports.